Hexamethonium in hypertensive encephalopathy - Peralta V., Aurelio (1955)
Routine treatment of hypertension through new powerful sympatholytic agents in order to achieve the reduction of blood pressure for long periods of time and in the hope of preventing vascular impairment is usually practiced by some and used with many other reserves. Instead, there are compelling indications to lower blood pressure, such as hypertensive encephalopathy, sub-arachnoid haemorrhage and left heart failure.